2008
DOI: 10.2320/matertrans.mov2007315
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Magnesium-Aluminum Based Alloys Containing Strontium

Abstract: The mechanical properties and processing performances of conventional magnesium alloys still could not meet the need of important application fields due to some demerits, such as poor formability, low creep resistance and unsatisfactory strength at elevated temperature. Recent investigations have shown that additions of strontium to magnesium alloys are effective in improving creep resistance of the alloys at temperatures above 150 C, and some new types of magnesium alloys containing strontium have been develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A further improvement in mechanical properties has been A.Lakshmanan Pillai, G.R.Jinu, G.Karthikeyan Fabrication and Tribological Behaviour of Mg-TiO 2 Composites required to extend the application of magnesium alloys [3,4]. Several researchers reported that the addition of hard ceramic particles to magnesium resulted in better wear resistance and improved mechanical properties and thermal stability [5][6]. Magnesium is about by one third lighter than aluminium and by two thirds than titanium.…”
Section: Introductionmentioning
confidence: 99%
“…A further improvement in mechanical properties has been A.Lakshmanan Pillai, G.R.Jinu, G.Karthikeyan Fabrication and Tribological Behaviour of Mg-TiO 2 Composites required to extend the application of magnesium alloys [3,4]. Several researchers reported that the addition of hard ceramic particles to magnesium resulted in better wear resistance and improved mechanical properties and thermal stability [5][6]. Magnesium is about by one third lighter than aluminium and by two thirds than titanium.…”
Section: Introductionmentioning
confidence: 99%
“…Mg-Al-based alloys are the most common and economic commercial magnesium alloys to which many grain refining methods have been developed, including superheating, Elfinal, carbon inoculation and addition of micro-alloying elements [4][5][6][7][8][9][10][11][12][13][14][15][16]. Among them, carbon inoculation is known to be the most effective grain refining method for operating at a low temperature and less fading with long-time holding.…”
Section: Introductionmentioning
confidence: 99%
“…Many new types of magnesium alloys are being developed in the world in order to further improve the mechanical properties and processing performances of the magnesium alloys [5][6][7] . However, conventional methods for developing new alloys need a lot of experimental work and take long time.…”
Section: Introductionmentioning
confidence: 99%